Revisando os efeitos da concentração de oxigênio sobre o desenvolvimento embrionário - Sobrinho, David Barreira Gomes [UNESP]; Oliveira, João Batista Alcântara [UNESP]; de Carvalho, Bruno Ramalho; Franco Junior, Jose Gonçalves [UNESP] (My University, 2012)
Despite the fact that the processes of embryo development and implantation of mammals do not occur in atmospheric tension in vivo, it is common practice in laboratories for in vitro fertilization (IVF) the culture of embryos in an oxygen tension of 20%. The discrepancy between the tensions of oxygen leads to important discussions about their effects in vitro embryo development. It is believed that the culture of embryo in atmospheric oxygen tension can be detrimental to the quality of the data for predisposing them to the negative interference of reactive oxygen species (ROS), resulting in oxidative stress, leading to deleterious effects on metabolism embryo gene expression and blastocysts grown in those conditions. Faced with arguments for and against the culture of embryos in vitro oxygen tensions similar to those found in vivo, this revies article aims to condense and discuss the literature concerning the influence of oxygen tension on the quality of in vitro culture.
Reviewing the effects of oxygen tension on embryo development
Keywords: Embryo culture; Gas atmosphere; IVF/ICSI; Low tension oxigen; Reactive oxygen species; reactive oxygen metabolite; blastocyst; cell growth; embryo culture; embryo development; fertilization in vitro; gene expression; in vitro study; in vivo study; medical literature; metabolism; nidation; oxidative stress; oxygen tension